Open Chain Polyarsenides of the Lanthanides. Issue 31 (9th May 2018) - Schoo, Christoph; Köppe, Ralf; Piesch, Martin; Gamer, Michael T.; Konchenko, Sergey N.; Scheer, Manfred; Roesky, Peter W.
Abstract: The reaction of [(Cp′′′Co)2 (μ, η 2:2 ‐As2 )2 ] with the decamethylsamarocenes [Cp*2 Sm(THF)2 ] or [Cp*2 Sm], or the bis(tetramethyl‐ n ‐propyl)samarocene [(C5 Me4 ( n ‐propyl))2 Sm] resulted in the mixed d/f polyarsenides [(Cp′′′Co)2 As4 Sm(η 5 ‐C5 Me4 R)2 ] (R=Me, n ‐propyl). They are the first structural representatives of open chain‐like polyarsenides as ligands in the coordination sphere of lanthanides. Their formation can be explained by an intramolecular As–As coupling within the cobalt polyarsenide complex after reduction by the divalent samarium complex. Density functional theory calculations give insight into the structural change of the (As2 )2 unit in [Cp′′′Co(μ, η 2:2 ‐As2 )2 ] upon reduction. Abstract : Chain gang : The reduction of [(Cp′′′Co)2 (μ, η 2:2 ‐As2 )2 ] with the samarocenes, [(C5 Me4 R)2 Sm(THF) n ] (R=Me, n =0, 2; n ‐propyl, n =0) resulted in [(Cp′′′Co)2 As4 Sm(C5 Me4 R)2 ]. These products are the first examples of d/f metal compounds with an open chain‐like polyarsenide structure.